Development and Validation of the Short-LIMOS for the Acute Stroke Unit—A Short Version of the Lucerne ICF-Based Multidisciplinary Observation Scale - Ottiger, Beatrice; Vanbellingen, Tim; Cazzoli, Dario; Nyffeler, Thomas; Veerbeek, Janne M. (Frontiers in Rehabilitation Sciences, 2022)
Introduction: At hospital stroke units, the time available to assess the patient’s limitations in activities and participation is limited, although being essential for discharge planning. Till date, there is no quick-to-perform instrument available that captures the patient’s actual performance during daily activities from a motor, cognitive, and communication perspective within the International Classification of Functioning, Disability and Health (ICF) framework. Therefore, the aim was to develop and validate a shortened version of the Lucerne ICF-Based Multidisciplinary Observation Scale (Short-LIMOS) that observes the patient’s performance across ICF-domains and is applicable in the context of an acute stroke unit. Methods: The Short-LIMOS was developed by reducing the original 45-item LIMOS to the ten most important items using a multivariable linear regression ANOVA with data of 836 stroke patients collected during inpatient neurorehabilitation. The Short-LIMOS’s reliability and validity were evaluated with data of 416 stroke patients in the acute stroke unit. Results: A significant equation (F(10,825) = 232.083) with R2 of .738 was found for the following ten items for the Short-LIMOS: maintaining a body position (d415), changing basic body position (d410), climbing stairs (d4551), eating (d550), dressing (d540), communicating with - receiving - written messages (reading) (d325), applying knowledge, remembering facts (d179), solving complex problems (d1751), making simple decisions (d177), and undertaking a simple task (d2100). Principal component analysis revealed a Short-LIMOS motor and a Short-LIMOS cognition/communication component. The Short-LIMOS had a high internal consistency and good test-retest reliability. A moderate construct validity was shown by the significant correlation with the Barthel Index. The Short-LIMOS had neither floor nor ceiling effects. Discussion and conclusion: The developed Short-LIMOS was found to be reliable and valid within a population of (hyper)acute and subacute stroke patients. The added value of this multidisciplinary assessment is its comprehensiveness by capturing the patient’s actual performance on the motor, cognitive, and communication domain embedded in an ICF-framework in less than ten minutes.